STEADY-STATE TEMPERATURE FIELD AND STRESS FIELD ANALYSIS OF AUTOCLAVE TOOTH-LOCKED QUICK OPENING STRUCTURE - DU ZhaoXin; LI HaiJing; FU Yang; GAO BingJun (Jixie qiangdu)
In order to provide accurate temperature field of autoclave,and make preparation for stress analysis,temperature of autoclave tooth-locked quick opening structure was measured. Using ANSYS to simulate the temperature field,the result is compared with the measured data. It shows that the simulation result is consistent with the actual situation. The strength and fatigue life were evaluated by JB4732-1995,evaluation results meet the requirements.